Cosmogenic radiation nuclides in archaeology : a response to Phillips et al. - Bednarik, Robert G.
Various methods have been employed in the attempt to date rock-art. Here Robert Bednarik offers a critique of the cosmogenic radiation nuclides method, and its application to the Côa petroglyphs.